Profiling of the glycaemic index of the underutilised vegetables - Thai, Ngoc Ro (2017)
Glycaemic Index is a term used to describe the effect on blood glucose of consuming a carbohydrate rich meal. It is a measure of the rise in blood glucose following consumption of a test food relative to a reference food. Various associations have been found between dietary GI and a number of chronic diseases.